Las presunciones jurídicas - Abache Carvajal, Serviliano (Revista de Derecho, 2019)
Juridical presumptions are studied from a merely dogmatic approach, starting with the revision of the subject from the problem presented by facts and their evidence, moving on to covering issues of greater relevance in this category iuris: justification, nature, concept and typology; their relevance is then analyzed on the processal context of the evidentiary activity, to then comment on their configuration in the particular frame of Tributary Law, as well as their relationship and differences —from the juridical conceptualization technical— with other con similar figures: evidence, fictions, and tributary assessment norms; and finally a brief review is done of their positive regulation in Venezuelan juridical array.